Philosophy of the world and philosophy of Karl Löwith as a precursor and incentive to the idea of integrative bioethics - Selak, Marija (Array, 2011)
Traditional cosmology, once used to explain the world, was suppressed by the domination of science over philosophy which happened after their separation. Nowadays, scientific (in terms of natural sciences) cosmology is given the advantage in answering the question what is the world, while the "non-empirical" catholicity (the basic characteristic of traditional cosmology) became useless. Encouragement of one’s effort to re-establish the category of catholicity can be found in the idea of integrative bioethics on one side and in the philosophy of the world on the other. In this paper the relation between the idea of integrative bioethics and the philosophy of the world will be established through philosophical discussions which were held in Augsburg and in Zagreb (1988, 1990, 1993) and also with reliance on understanding the world in philosophy of Karl Löwith.